2020
DOI: 10.1136/bmjopen-2019-034424
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of psychological, psychoeducational and psychosocial interventions to prevent postpartum depression in adolescent and adult mothers: study protocol for a systematic review and meta-analysis of randomised controlled trials

Abstract: IntroductionThe prevalence of postpartum depression (PPD) is 17%, and the incidence is 12% worldwide. Adverse consequences for mothers and babies have been associated with this disease. To assess the effectiveness of psychological, psychoeducational and psychosocial interventions in preventing PPD, a systematic review and meta-analysis (SR/MA) will be conducted.Methods and analysisA SR/MA will be performed following the indications of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
(29 reference statements)
0
13
0
4
Order By: Relevance
“…Heterogeneity will also be tested by the I 2 statistic, which can quantify the heterogeneity ranging from 0% (no heterogeneity) to 100% (the differences between the effect sizes can completely be explained by chance alone), and the interpretations of the percentages are as follows: 0%–40% indicates potentially unimportant heterogeneity, 30%–60% indicates moderate heterogeneity, 50%–90% indicates substantial heterogeneity and 75%–100% indicates considerable heterogeneity. 35 To explore the heterogeneity across studies, subgroup analysis will be performed using a mixed effects model according to the following variables: age (young people vs adults), ethnicity (impact on mental health of patients from a specific ethnic group vs not) and psychological distress (mild vs moderate vs severe).…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Heterogeneity will also be tested by the I 2 statistic, which can quantify the heterogeneity ranging from 0% (no heterogeneity) to 100% (the differences between the effect sizes can completely be explained by chance alone), and the interpretations of the percentages are as follows: 0%–40% indicates potentially unimportant heterogeneity, 30%–60% indicates moderate heterogeneity, 50%–90% indicates substantial heterogeneity and 75%–100% indicates considerable heterogeneity. 35 To explore the heterogeneity across studies, subgroup analysis will be performed using a mixed effects model according to the following variables: age (young people vs adults), ethnicity (impact on mental health of patients from a specific ethnic group vs not) and psychological distress (mild vs moderate vs severe).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Statistical analyses will be carried out using the Statistical Package for the Social Sciences (SPSS), V.18.0 (SPSS). Standardised mean differences (SMDs) and 95% CI will be used to calculate the effect sizes, as we expect that most of the observational studies 35 included in our meta-analysis have reported differences in psychological symptoms. All effect sizes will be transformed into a common metric in order to make them comparable across studies-the biascorrected standardised difference in means (Hedges' g).…”
Section: Assessment Of Publication Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Los síntomas más comunes de la depresión posparto son el estado de ánimo triste, dificultad para concentrarse, fatiga, falta de interés por el bebé, sentimiento de ser una mala madre, insomnio, miedo a lastimarse a sí misma o al bebé y pérdida de interés o placer en la vida 13 . Se han descrito también llanto frecuente, falta de apetito, síntomas somáticos múltiples, incapacidad para afrontar situaciones estresantes, baja autoestima e ideación suicida 14 .…”
Section: Introductionunclassified
“…Una forma de reducir la carga de enfermedad que provoca la depresión es disminuir la incidencia de nuevos casos, objetivo que puede lograrse mediante intervenciones preventivas 13 , que implican el tratamiento de un gran número de mujeres de la población general que pueden no estar en riesgo o que involucran a población de alto riesgo 31 . La mayoría de las terapias preventivas disponibles se basan en enfoques no farmacológicos de tipo psicológicos, psicoeducativos, psicosociales y físicos 13,32 .…”
Section: Introductionunclassified